On reading well : finding the good life through great books - Prior, Karen Swallow (Brazos Press, 2018)
Reading great literature well has the power to cultivate virtue. Great literature increases knowledge of and desire for the good life by showing readers what virtue looks like and where vice leads. It is not just what one reads but how one reads that cultivates virtue. Reading good literature well requires one to practice numerous virtues, such as patience, diligence, and prudence. And learning to judge wisely a character in a book, in turn, forms the reader's own character.